2005
DOI: 10.1007/s10802-005-3568-2
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Peer-Level Effects of a Small-Group Selected Prevention on Aggression in Elementary School Children: An Investigation of the Peer Contagion Hypothesis

Abstract: Examined peer contagion in small group, selected prevention programming over one school year. Participants were boys and girls in grades 3 (46 groups, 285 students) and 6 (36 groups, 219 students) attending school in low-resource, inner city communities or moderate resource urban communities. Three-level hierarchical linear modeling (observations within individuals within groups) indicated that individual change in aggression over time related to the average aggression of others in the intervention group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 68 publications
3
76
0
3
Order By: Relevance
“…Following the procedure of previous studies (Boxer et al 2005), we used a composite measure of participants' aggressive behavior, made up of the combination of the reactive aggression subscale of the Reactive Proactive Aggression Questionnaire (RPQ; Raine et al 2006) and a peer nomination instrument developed by Crick (1997). The reactive aggression subscale of the RPQ consists of 11 items ("How often have you become angry or mad when you don't get your way?").…”
Section: Methodsmentioning
confidence: 99%
“…Following the procedure of previous studies (Boxer et al 2005), we used a composite measure of participants' aggressive behavior, made up of the combination of the reactive aggression subscale of the Reactive Proactive Aggression Questionnaire (RPQ; Raine et al 2006) and a peer nomination instrument developed by Crick (1997). The reactive aggression subscale of the RPQ consists of 11 items ("How often have you become angry or mad when you don't get your way?").…”
Section: Methodsmentioning
confidence: 99%
“…6,7,8,9,49 This may be attributable to so-called 'discrepancy proportional peer influence' so that the behaviour of those at the extremes is drawn toward the group mean. 50 If this is true, it requires the presence of some less overtly deviant peers in the therapeutic group. Their absence could explain the failure of an intervention involving a group of children all of whom scored at or above the 95 th centile for teacher-rated aggression.…”
Section: Discussionmentioning
confidence: 99%
“…That is, initially highly aggressive children showed decreases of such behaviors to the mean level present in the group. However, a reverse pattern was found for initially non-aggressive children who became more aggressive, up to level that was shared with the group aggregate (Boxer et al 2005). Analysis of the mechanisms suggested that peer contagion processes within the small groups may have caused the increases in aggression among initially low aggressive children (Boxer et al 2005).…”
Section: Group-based Programs With Targeted Populationsmentioning
confidence: 92%